2019
DOI: 10.1007/s12576-019-00691-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxin and calcitonin secretion into thyroid venous blood is regulated by pharyngeal mechanical stimulation in anesthetized rats

Abstract: The effects of the pharyngeal non-noxious mechanical stimulation on the secretion of immunoreactive thyroxin (iT4), immunoreactive calcitonin (iCT), and immunoreactive parathyroid hormone (iPTH) into thyroid venous blood were examined in anesthetized rats. Secretion rates of iT4, iCT, and iPTH were calculated from their concentration in thyroid venous plasma and the plasma flow rate. A mechanical stimulation was delivered to the pharynx by a rubber balloon placed on the tongue that was intermittently pushed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Among the possible candidates, the following regions need specific attention: (i) cholinergic neurons in the striatum and the basal forebrain projecting to wide areas in pallium (or cortex in mammals) ( Ahmed et al. 2019 ), (ii) cholinergic neurons in nucleus isthmi parvocellularis (or pedunculo-pontine tegmental nucleus) projecting to optic tectum (superior colliculus) ( Knudsen 2011 ), and (iii) preganglionic cholinergic terminals of parasympathetic nerve acting on thyroid gland ( Iimura et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible candidates, the following regions need specific attention: (i) cholinergic neurons in the striatum and the basal forebrain projecting to wide areas in pallium (or cortex in mammals) ( Ahmed et al. 2019 ), (ii) cholinergic neurons in nucleus isthmi parvocellularis (or pedunculo-pontine tegmental nucleus) projecting to optic tectum (superior colliculus) ( Knudsen 2011 ), and (iii) preganglionic cholinergic terminals of parasympathetic nerve acting on thyroid gland ( Iimura et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as nAChR is widespread in the brain and body103105, several brain regions/organs must be considered. Among the possible candidates, the following regions need specific attention: (1) cholinergic neurons in the striatum and the basal forebrain projecting to wide areas in pallium (or cortex in mammals)106, (2) cholinergic neurons in nucleus isthmi parvocellularis (or pedunculo- pontine tegmental nucleus) projecting to optic tectum (superior colliculus)107109, and (3) pre-ganglionic cholinergic terminals of parasympathetic nerve acting on thyroid gland110. If (1) is the case, involvement of telencephalon in the BM predisposition should be considered as delayed GABA switch may be an underlying factor in the brain areas along with IMM, arco and tectum.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, endogenous CT has also been shown to play a role in regulating postprandial hypercalcemia [ 17 ]. A recent study revealed that pharyngeal mechanical stimulation, like during eating, increases iCT secretion by a neurogenic reflex through the SLN [ 18 ]. Therefore, stimulation of the SLN during daytime, when rats do not eat, was expected to be effective in inhibiting bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no statistically significant findings between OVX SLN stimulation and OVX sham stimulation groups in any of the results on bone histomorphometry (Table 2). through the SLN [18]. Therefore, stimulation of the SLN during daytime, when rats do not eat, was expected to be effective in inhibiting bone loss.…”
Section: Chronic Sln Stimulation In Conscious Rats Partially Improvedmentioning
confidence: 99%